Bradyrhizobium japonicum doses and fertilizer from cupuaçu residues: seedling quality, chlorophyll content, and photosynthetic efficiency in Mezilaurus itauba - Aline das Graças Souza; Edna Ursulino Alves; Thiago Jardelino Dias; Wellington Farias Araujo; Oscar Jose Smiderle (Acta Scientiarum. Agronomy, 2025)
This study evaluates the optimal dose for maximum technical efficiency of Bradyrhizobium japonicum (B. japonicum), both with and without a fertilizer derived from cupuaçu residues (FERCup), on the early growth, seedling quality, and physiological metrics of Mezilaurus itauba in the northern Amazon. We assessed several parameters: shoot height (SH, cm), stem diameter (SD, mm), shoot dry mass (SDM, g plant-1), root dry mass (RDM, g plant-1), total dry mass (TDM, g plant-1), Dickson Quality Index (DQI), chlorophyll a (CHL a, μg mL-1), chlorophyll b (CHL b, μg mL-1), total chlorophyll (CHL total, μg mL-1), Nitrogen Balance Index (NBI), specific leaf area (SLA, cm² g-1), and leaf area ratio (LAR, m² g-1). A B. japonicum dose of 0.30 mL L-1, with or without FERCup, enhanced seedling quality and robustness in M. itauba under the study conditions. Including FERCup at these doses significantly improved the morphological traits of the M. itauba seedlings. Additionally, B. japonicum doses of 0.2 and 0.4 mL L-1 with FERCup positively impacted all physiological indices in M. itauba seedlings 180 days post-transplant.